How to improve the customer experience when buying cosmetics online? - Madeline, Charlotte Marie Françoise (2022)
The cosmetics industry is currently facing major challenges, especially with the emergence of new trends and the growing importance of online shopping. The consumer experience when buying cosmetics online is set to evolve in order to fill some of the gaps that this dissertation aims to address. Therefore, the purpose of this thesis is to improve the customer experience when buying cosmetics online by capturing the online customer journey and proposing solutions to enhance it. In order to achieve this objective, this essay firstly provides an overview of the current cosmetics market, an analysis of the key concepts related to customer experience and a study of previous research regarding customer journey maps. Following this, a qualitative research study involving twenty interviews enabled the collection of precious customer data which was then analyzed using the Critical Incident Method to define typical customer journeys. After the study of these typical consumer paths, customer journey maps were developed to visualize their pain points and opportunities for improvement. The results of this study suggest various enhancements along the customer journey such as developing websites' UX, providing accessible and qualitative visual content (videos, photos, etc.), implementing personalized diagnostics, limiting delivery fees, simplifying customer feedback emails and adapting loyalty programs to current consumer needs etc. Thus, the visual tools provided by the customer journey maps allowed us to suggest solutions adapted to each phase of the online cosmetics purchase journey. These suggestions for improvement are summarized in a final customer journey map that includes the different phases, the consumer's actions and associated touchpoints, as well as their state of mind throughout the journey. Finally, this research provides valuable insight for cosmetic brands wishing to improve their online sales performance over the long term by understanding their customers' behaviors, needs and expectations.